Anti‐herbivore defences and insect herbivory: Interactive effects of drought and tree neighbours. (14th March 2018) - Castagneyrol, Bastien; Jactel, Hervé; Moreira, Xoaquín
Abstract: How much a plant is attacked by insect herbivores likely depends on its apparency and ability to produce defensive traits, which may be modified by neighbouring plants and abiotic conditions. Yet, how much the direct and trait‐mediated effects of neighbours on herbivory is modified by abiotic factors is still unknown. By using a tree diversity experiment in SW France, we measured leaf insect herbivory (chewers and miners), nutritional quality (water content, C/N ratio, sugar and starch content) and chemical defences (total polyphenolics and condensed tannins) on birch ( Betula pendula ) trees growing in monocultures and mixtures with oak, pine or both species. We alleviated water stress by irrigating trees in half of the plots while trees remained unwatered (i.e. drought‐stressed) in the other half. Overall, insect herbivory was higher among heterospecific neighbours, which corresponds to associational susceptibility. Consistent with this finding, leaves had lower amount of anti‐herbivore defences among heterospecific neighbours. In turn, insects caused more damage in drought‐stressed conditions, but such effect was independent of leaf chemistry. We also found that the effect of tree species diversity on herbivory was contingent of drought conditions as associational susceptibility only occurred in drought‐stressed trees. The independent and interactive effects of neighbour diversity and irrigation on leaf herbivory remained significant after accounting for birch apparency and leaf chemistry, suggesting that unmeasured plant traits or some other mechanisms not associated with plant trait variation and apparency might be involved in the observed herbivory patterns. Synthesis . By demonstrating that associational effects are contingent upon abiotic constraints, we bring new insights into our understanding of the mechanisms driving diversity—resistance relationships across climatic gradients. Abstract : We tested if and how drought modifies the effect of heterospecific neighbouring trees on insect herbivory of birch. We showed that birch neighbours modify (1) its accessibility and apparency to herbivores and (2) the quality of its leaves, regardless of water stress. (3) Herbivory was higher in the presence of heterospecific neighbours, but only in stressed birch trees, which was partly due to (4) neighbour‐mediated changes in leaf chemistry, (5) regardless of birch apparency.